Glycyrrhiza uralensis and Semilicoisoflavone B Reduce A Secretion by Increasing PPAR Expression and Inhibiting STAT3 Phosphorylation to Inhibit BACE1 Expression - Gu, Ming-Yao; Chun, Yoon Sun; Zhao, Dong; Ryu, Shi Yong; Yang, Hyun Ok (John Wiley & Sons Ltd., 2018)
ScopeGlycyrrhiza uralensis extract (GUE) has been reported to improve amyloid beta (A)-induced cognitive deficits in mice. However, the mechanisms underlying this effect and the components involved have not been previously explored. Extracellular A plaques are one of the major pathological hallmarks of Alzheimer's disease (AD). Therefore, decreasing A levels is one strategy for preventing the etiology of AD. This study aims to test the effect of GUE and semilicoisoflavone B (SB) on A secretion and investigates the mechanism underlying this effect. Methods and resultsGUE and its bio-activated compound SB reduce A secretion. We find that this effect contribute to the downregulation of the -secretase-1 (BACE1) protein and mRNA. In a subsequent mechanism study, we find that GUE and SB regulate BACE1 transcription factors by inducing the expression of peroxisome proliferator activated receptor (PPAR) and inhibiting the phosphorylation of signal transducer and activator of transcription 3. In addition, the effect of GUE and SB on BACE1 expression and A secretion are attenuated by treatment with PPAR-siRNA or its antagonist, GW9662. ConclusionThese findings indicate that GUE and SB may function as PPAR agonists, thereby inhibiting BACE1 expression and ultimately reducing the secretion of A.